Popular press reveals controversy and misconceptions regarding quinoa and food security - Ambrozek, C.; Zorilla, M. (European SAVE Foundation (Germany), 2014)
Agricultural biodiversity is a strategic asset, particularly for rural people. Agricultural biodiversity has a role in increasing agricultural sustainability, maintaining resilience at the landscape level, facilitating the ability of communities to adapt to a changing climate, improving their diets and nutritional outcomes, and increasing their food security. Diverse traditional crop species can have higher nutritional values than some major crops, as well as having multiple uses for the household. Considering that in 2010-2012 there were 870 million people who went hungry, 840 million who were obese and 2 billion who suffered from at least one micronutrient deficiency, as many tools as possible to tackle this triple malnutrition challenge of hunger, obesity and nutrient deficiencies are needed.